Interleukin-10 production by B cells is regulated by cytokines, but independently of GATA-3 or FoxP3 expression - Bohacova, Pavla; Kossl, Jan; Hajkova, Michaela; Hermankova, Barbora; Javorkova, Eliska; Zajicova, Alena; Krulova, Magdalena; Holan, Vladimir (Cellular immunology, 2020)
The knowledge of mechanisms of regulation of IL-10 production by B cells remains still very limited. We show here that highly purified mouse B cells stimulated with LPS produce significant levels of IL-10, but Bregs in our model do not express detectable level of either Foxp3 or GATA-3. Nevertheless, IL-10 production by B cells is regulated by cytokines. In activated B cells, IL-10 production was significantly enhanced by IFN-γ and decreased in the presence of IL-4 or TGF-β. These findings are in sharp contrast with the observations in T cells, where IL-10 production correlates with GATA-3 or FoxP3 expression, and the cytokines regulate IL-10 production in a reverse manner than in activated B cells. These results thus show that the production of IL-10 by Bregs is regulated by cytokines independently of the expression of GATA-3 and FoxP3, which is clearly different from GATA-3-dependent IL-10 production by activated Th2 cells and FoxP3 expression in IL-10-producing Tregs.
Keywords: Female; interferon gama; myši; faktor 1 indukovatelný hypoxií - podjednotka alfa; Animals; forkhead transkripční faktory; kultivované buňky; Forkhead Transcription Factors; Cells, Cultured; T-Lymphocytes, Regulatory; Hypoxia-Inducible Factor 1, alpha Subunit; Lymphocyte Activation; B-Lymphocytes, Regulatory; interleukin-10; interleukin-4; regulační T-lymfocyty; regulační B-lymfocyty; Interferon-gamma; transkripční faktor GATA3; Th2 Cells; Th2 buňky; transformující růstový faktor beta; lipopolysacharidy; Mice, Inbred BALB C; Mice; zvířata; Lipopolysaccharides; aktivace lymfocytů; Interleukin-4; myši inbrední BALB C; Transforming Growth Factor beta; ženské pohlaví; Interleukin-10; GATA3 Transcription Factor